REPRESENTASI BERITA POLITIK DI TELEVISI DALAM TINJAUAN PERSPEKTIF INDEPENDENSI BERITA - Hadiati, Hadiati (JURNAL PUSTAKA KOMUNIKASI, 2018)
The main aim of this study is to investigate and critically examines the view of the political news representation on Jakarta gubernatorial election 2017. This study employed critical discourse analysis to investigate the power bias in news coverage of Jakarta election on TV One and Metro TV and seeks to examine the ideology behind the television media. A critical discourse analysis of the data revealed several findings. First, the television media coverage on the political news of Jakarta election in the form of text was ambiguous. While the political news has been positioned around the public sector that supposed to be politically neutral, nevertheless the media still produce subjective discourses. Second, the existence of certain interest groups has a significant effect on text production process in media. Third, the production of texts and the discourse practice in the media coverage of Jakarta's gubernatorial election are influenced by the particular regime interests, since the editorial room and the television studio are still considered as places of power. Fourth, the insensitivity of media objectivity is closely related to the sociocultural context that has developed in the society. The sociocultural profession of journalists in the Indonesian society still tends to be perceived as belonging to the power of incumbency. Thus, the political news representation remains heavily influenced by power.The power bias which is a problem in a democratic society, actually still growing and remaining in the television media, especially when representing the political news. The media’s potential to construct reality cannot be ignored. In other words, the change of democratic political system and media liberalization is not directly proportional to the expected changing in the attitude of the media in representing unbiased political news.